Journalism History and Digital Archives - Bodker, Henrik (Taylor & Francis, 2021)
"This book showcases various ways in which digital archives allow for new approaches to journalism history. The chapters in this book were selected based on three overall objectives: 1) research that highlights specific concerns within journalism history through digital archives; 2) discussions of digital methodologies, as well as specific applications, that are accessible for journalism scholars with no prior experiences with such approaches; and 3) that journalism history and digital archives are connected in other ways than through specific methods, i.e., that the connection raises larger questions of historiography and power. The contributions address cases and developments in Asia, South and North America and Europe; and range from long-range, big-data, machine-leaning and topic modelling studies of journalistic characteristics and meta-journalistic discourses to critiques of archival practices and access in relation to gender, social movements and poverty. The chapters in this book were originally published as a special issue of Digital Journalism."